2020
DOI: 10.1017/s0007114520000148
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-related genes and cardiometabolic markers in healthy children: a Mendelian randomisation study

Abstract: Observational studies show associations between low serum 25-hydroxyvitamin D (25(OH)D) and cardiometabolic risk markers. This Mendelian randomisation study examined associations between cardiometabolic markers in children and SNP in genes related to vitamin D metabolism (DHCR7; group-specific complement (GC); cytochrome P450 subfamily IIR1 (CYP2R1); and CYP24A1) and action (CYP27B1 and VDR). In 699 healthy 8–11-year-old children, we genotyped eleven SNP. We generated a genetic risk score based on SNP associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Lopez-Mayorga et al did not confirm the linkage of VDR gene three polymorphisms with cardiometabolic risk. However, the study was performed on children [ 30 ]. Nevertheless, the conclusion about the association of AGTR1 (rs5186) and VDR (rs2228570) with EAH is questionable and differs in populations due to various designs and patterns of research [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lopez-Mayorga et al did not confirm the linkage of VDR gene three polymorphisms with cardiometabolic risk. However, the study was performed on children [ 30 ]. Nevertheless, the conclusion about the association of AGTR1 (rs5186) and VDR (rs2228570) with EAH is questionable and differs in populations due to various designs and patterns of research [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed that the rs6068816T allele is associated with higher levels of 25(OH)D concentration and a lower risk of NSCLC, whereas no such association was found for the rs2296241 allele ( 34 ). However, inconsistent results were found in other studies, which found that both the rs6068816 and rs2296241 polymorphisms were not associated with 25(OH)D concentration levels ( 35 , 36 ). Because of a synonymous polymorphism, rs6068816 and rs2296241 cannot alter the amino acid sequence of CYP24A1 .…”
Section: Discussionmentioning
confidence: 70%
“…After primarily screening titles and abstracts for eligibility, 70 records were excluded, leaving 51 research articles for full-text secondary screening. Finally, only 11 research articles were chosen after satisfying the inclusion and exclusion criteria [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. These included five Mendelian randomization studies [ 42 , 43 , 44 , 46 ], two case–control studies [ 47 , 49 ], two cohort studies [ 48 , 50 ], and three cross-sectional studies [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, only 11 research articles were chosen after satisfying the inclusion and exclusion criteria [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. These included five Mendelian randomization studies [ 42 , 43 , 44 , 46 ], two case–control studies [ 47 , 49 ], two cohort studies [ 48 , 50 ], and three cross-sectional studies [ 40 , 41 , 42 ]. Reasons for exclusion included the following: no calculation of vitamin D GRS, but the calculation of a polygenetic risk score instead ( n = 12); GRS not based on vitamin D-related SNPs ( n = 9); only serum vitamin D concentration studied as an outcome ( n = 14); genetic predisposition of individual SNPs studied only ( n = 3); and the use of SNPs associated with high 25(OH)D levels ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation